Meningkatkan Aktivitas Dan Hasil Belajar Ipa Menggunakan Kombinasi Model PBL, SAVI, Dan MAM Di SDN Percontohan Surgi Mufti 5 Banjarmasin - Sulistia Rahmah; Ahmad Muhyani Rizalie (CV. ITTC INDONESIA, 2023)
This class action research was conducted because of the low activity and learning outcomes of fifth grade students at SDN Percontohan Surgi Mufti 5 Banjarmasin. This problem is caused by one-way learning, lack of learning material sources, students are not motivated to find out, lack of student involvement in learning, students only do what the teacher tells them, and tend to wait for problem solving from the teacher. This causes learning outcomes to decline. To overcome these problems, researchers combined the Problem Based Learning (PBL), Somatic Auditory Visualization Intellectualy (SAVI), and Make a Match models. This Classroom Action Research (CAR) was conducted using a qualitative approach and carried out for three meetings. The types of data used are qualitative and quantitative data in the form of observations of teacher activities, student activities, and student learning outcomes tests during the learning process. Data analysis was calculated based on a percentage scale and predetermined indicators of classical learning completeness. The research findings showed that at each meeting students' activities increased. Student learning outcomes at each meeting gradually increased in the evaluation of meeting 1 to meeting 3.